1994
DOI: 10.1073/pnas.91.10.4456
|View full text |Cite
|
Sign up to set email alerts
|

High-affinity binding of short peptides to major histocompatibility complex class II molecules by anchor combinations.

Abstract: We have previously identified four anchor positions in HLA-DRB1*0101-binding peptides, and three anchors involved in peptide binding to DRB1*0401 and DRB1*11O1 molecules, by screening of an M13 peptide display library (420 million independent nonapeptides) for DRbinding activity. In this study, high stringency screening of the M13 library for DRB1*0401 binding has resulted in identification of three further anchor positions. Taken together, a peptide-binding motif has been obtained, in which six of seven posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
75
0
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 25 publications
11
75
0
3
Order By: Relevance
“…Relative display levels of HLA-DR1 with the different peptides, presumably reflecting relative binding affinity between the MHC-II protein and peptide, follow the order Phe ≈ Tyr≈ Trp > Met > Leu ≈ Ile > Val, whereas all other amino acids tested yield very low binding to HLA-DR1. These results show striking agreement with binding preferences previously determined using quantitative in vitro peptide-binding assays (21), qualitative phage display and bioinformatics methods (23,31), and structure-based computational prediction approaches (32). Most importantly, the yeast codisplay method appears to demonstrate quantitative ability paralleling that of competitive binding assays with purified proteins and soluble peptides (21) while retaining the ease of rapid recombinant expression without component purification and compatibility with high-throughput screening approaches.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Relative display levels of HLA-DR1 with the different peptides, presumably reflecting relative binding affinity between the MHC-II protein and peptide, follow the order Phe ≈ Tyr≈ Trp > Met > Leu ≈ Ile > Val, whereas all other amino acids tested yield very low binding to HLA-DR1. These results show striking agreement with binding preferences previously determined using quantitative in vitro peptide-binding assays (21), qualitative phage display and bioinformatics methods (23,31), and structure-based computational prediction approaches (32). Most importantly, the yeast codisplay method appears to demonstrate quantitative ability paralleling that of competitive binding assays with purified proteins and soluble peptides (21) while retaining the ease of rapid recombinant expression without component purification and compatibility with high-throughput screening approaches.…”
Section: Resultssupporting
confidence: 75%
“…A number of studies have assessed peptide-binding to MHC-II on the surface of intact APCs (12,13), whereas a routinely used in vitro approach entails purifying soluble recombinant MHC-II molecules from different expressing systems such as B cell lines (14), insect cells (15,16), yeast (17), or Escherichia coli (18)(19)(20) and then characterizing binding of these molecules to different peptides generated either chemically by solid phase synthesis or genetically by phage display (4,21). The labor-intensive preparation of soluble proteins, lengthy binding assays, or nonquantitative data generated (e.g., peptide abundance) limits the efficiency and throughput of these methods for mapping MHC-II binding specificities across the large number of existing alleles.…”
mentioning
confidence: 99%
“…For the complex with MAT peptide, no structure is available, but the peptide register and orientation appear to be the same as observed in the DR1-HA and DR3-CLIP complexes, based on studies of the effects of peptide substitution on the binding affinity (47)(48)(49). To minimize any interaction of the AMCA probe with the DR1-peptide binding reaction, we attached the probe to side chains at positions oriented away from the binding site, at position P2 (MAT), P3 (HA), and P8 (CLIP), numbered relative to the large hydrophobic side chain at P1 that binds into MHC binding site pocket 1 (13).…”
Section: Resultsmentioning
confidence: 99%
“…We therefore generated T cell clones from CII-immunized B10.DR4.Ncf1* mice in order to test these against CII peptides in which K 264 and/or K 270 had been substituted for arginine (R), since this has been found to be the preferred amino acid at position P2 for peptides binding to DRB1*0401 (29). We also performed binding studies, which confirmed that substitutions of lysine for arginine residues had minimal consequences for class II MHC peptide binding ( Figure 4A).…”
Section: B10mentioning
confidence: 99%